The Role of IFRS on Financial Reporting Quality and Global Convergence: A Conceptual Review - Musa, Auwalu (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2019)
This study examines the role of International Financial Reporting Standards on financial reporting quality and the global convergence. The IFRS adoption is already an issue of global relevance across countries of the world due to the quest for uniformity, reliability and comparability of financial statements of companies. The adoption of IFRS in Europe is an example of accounting quality across-borders with different institutional frameworks and enforcement rules. This allows investigating whether, and to what extent accounting regulation per se can affect the quality of financial reporting and leads to convergence in financial reporting. Specifically, the study review how the change in the recognition and measurement of firms operating accrual item, the loan loss provision, affects income smoothing behaviour and timely loss recognition. The study found that the IFRS convergence reduces the scope for earnings management, is related to more timely loss recognition and leads to more value relevant accounting measures. Thus, the study reviews background and guidance on the change in financial reporting quality following extensive IFRS adoption around the world countries. The study found that a difference in accounting quality is related to country’s overall infrastructure setting. The study also highlights the importance of investor protection for financial reporting quality and the need for regulators to design mechanisms that limit managers' earnings management practice. The study found from different literatures that the adoption of IFRS leads to higher quality of accounting numbers and improve foreign direct investment across countries.